Electronic health record analysis identifies kidney disease as the leading risk factor for hospitalization in confirmed COVID-19 patients - Matthew T. Oetjens; Jonathan Z. Luo; Alex R. Chang; Joseph B. Leader; Dustin N. Hartzel; Bryn S. Moore; Natasha T. Strande; H. Lester Kirchner; David H. Ledbetter; Anne E. Justice; David J. Carey; Tooraj Mirshahi (2020)
Background Empirical data on conditions that increase risk of coronavirus disease 2019 (COVID-19) progression are needed to identify high risk individuals. We performed a comprehensive quantitative assessment of pre-existing clinical phenotypes associated with COVID-19-related hospitalization. Methods Phenome-wide association study (PheWAS) of SARS-CoV-2-positive patients from an integrated health system (Geisinger) with system-level outpatient/inpatient COVID-19 testing capacity and retrospective electronic health record (EHR) data to assess pre-COVID-19 pandemic clinical phenotypes associated with hospital admission (hospitalization). Results Of 12,971 individuals tested for SARS-CoV-2 with sufficient pre-COVID-19 pandemic EHR data at Geisinger, 1604 were SARS-CoV-2 positive and 354 required hospitalization. We identified 21 clinical phenotypes in 5 disease categories meeting phenome-wide significance (P<1.60x10 -4 ), including: six kidney phenotypes, e.g. end stage renal disease or stage 5 CKD (OR = 11.07, p = 1.96x10 -8 ), six cardiovascular phenotypes, e.g. congestive heart failure (OR = 3.8, p = 3.24x10 -5 ), five respiratory phenotypes, e.g. chronic airway obstruction (OR = 2.54, p = 3.71x10 -5 ), and three metabolic phenotypes, e.g. type 2 diabetes (OR = 1.80, p = 7.51x10 -5 ). Additional analyses defining CKD based on estimated glomerular filtration rate, confirmed high risk of hospitalization associated with pre-existing stage 4 CKD (OR 2.90, 95% CI: 1.47, 5.74), stage 5 CKD/dialysis (OR 8.83, 95% CI: 2.76, 28.27), and kidney transplant (OR 14.98, 95% CI: 2.77, 80.8) but not stage 3 CKD (OR 1.03, 95% CI: 0.71, 1.48). Conclusions This study provides quantitative estimates of the contribution of pre-existing clinical phenotypes to COVID-19 hospitalization and highlights kidney disorders as the strongest factors associated with hospitalization in an integrated US healthcare system.